Overfeeding in the early postnatal period aggravates inflammation and hepatic insulin sensitivity in the 5α-dihydrotestosterone-induced animal model of PCOS - Veličković, Nataša; Mićić, Bojana; Teofilović, Ana; Milovanovic, Milena; Jovanović, Mirna; Djordjevic, Ana; Macut, Djuro; Vojnović Milutinović, Danijela (Frontiers in Endocrinology, 2024)
Background: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women of reproductive age and is closely associated with chronic low-grade inflammation and insulin resistance. To clarify the contribution of prepubertal weight gain to the development of insulin resistance in PCOS, we investigated the effects of early postnatal overfeeding on inflammatory and energy-sensing pathways as well as on markers of insulin signaling in the liver of the PCOS rat model.Methods: Obesity induced by overfeeding was achieved by reducing litter size, while the PCOSlike condition was developed by treatment with 5α-dihydrotestosterone (DHT). Western blot and qPCR were used to analyze the expression of pro-inflammatory transcription factors and cytokines, as well as markers of the energy sensing and insulin signaling pathways.The results showed that hepatic insulin sensitivity was impaired only in DHT-treated rats raised in small litters, as evidenced by increased phosphorylation of IRS1 on Ser307 and decreased expression of total IRS1. Postnatal overfeeding stimulated JNK1 activation independent of hyperandrogenemia; nevertheless, the synergistic effect of both factors triggered NLRP3 activation and increased IL1β expression in the small litter DHT-treated group. This proinflammatory state was accompanied by decreased activatory phosphorylation of AMPK and reduced levels of its protein targets.Overfeeding in the early postnatal period leads to a decrease in hepatic insulin sensitivity in the rat model of PCOS, which is associated with decreased activation of AMPK and stimulation of the hepatic NLRP3-IL1β signaling pathway. Accordingly, the inhibition of NLRP3 activation could provide a basis for the development of new therapeutic strategies for the treatment of insulin resistance in women with PCOS.